The Relationship between Sexual Self-concept and Sexual Function in Women of Reproductive Age Referred to Health Centers in Gorgan, North East of Iran - Tayebe Ziaei; Halimeh Farahmand Rad; Masoumeh Rezaei Aval; Gholamreza Roshandel (Journal of Midwifery & Reproductive Health, 2017)
Background & aim: The preservation and enhancement of the sexual function are the key elements of sexual health. One of the most important predictive factors of sexual behavior and function is sexual self-concept. This construct is defined as the individuals’ understanding and evaluation of their own sexual desires and orientations. The aim of the present study was to determine the correlation between the dimensions of sexual self-concept and sexual function in the women of reproductive age. Methods: This correlational descriptive study was conducted on 79 married women of reproductive age referred to the health centers in Gorgan, Iran. The sample size was determined using the sample size formula with a power of 90% and a confidence interval of 95%. The data collection tools included the Persian multidimensional sexual self-concept questionnaire included 23 items covering five dimensions (i.e., sexual anxiety, sexual fear, sexual self-efficacy, sexual self-esteem, and sexual satisfaction) and the Persian Female Sexual Function Index consisted of 19 items in six dimensions. Data analysis was performed using the Mann-Whitney U test and Spearman's rank correlation coefficient through the SPSS software (version 16). Results: The Spearman correlation test revealed a significant direct correlation between the sexual self-esteem and the positive dimensions of sexual function, including desire (P=0.002, r=0.3), arousal (P